An alternative measure of core inflation - Michael Pedersen (Danmarks Nationalbank, 2005)
We combine the ideas of the trimmed mean and the Edgeworth index to construct an alternative measure of core inflation named Trim of Most Volatile Components (TMVC). At each point of time this measure trims away the components of the price index, which have been most volatile in the past. TMVC tracks trend inflation better than other core inflation measures in the euro zone, but in the US the evidence is weaker.
Keywords: E31; C43; 330; core inflation; trimmedmean; Edgeworth index; TMVC; Inflationsrate; Kerninflation; Indexberechnung